Design of a curriculum for teaching speaking skills based on the concept of the modern curriculum at the Islamic Pen Institute at the 2nd State Islamic High School in Malang - Amin, Muhammad (Jurnal Pendidikan Bahasa Arab dan Budaya Islam, 2023)
The teaching of the Islamic Pen Institute for freshmen (tenth grade) in the first stage focused on teaching speaking skills. However, there is no curriculum in its modern concept. The teaching procedure is based on the books agreed upon in the work consultation before entering the new school year. In addition, there is the problem of writing the items of the end-of-year test questions. Therefore, it is important to design the curriculum for teaching speaking skills at the Islamic Pen Institute to address the existing problems and achieve the desired goals. Research objectives: 1) Describe how to design the curriculum for teaching speaking skills at the Islamic Pen Institute; 2) Describe the specifications of the curriculum for teaching speaking skills at the Islamic Pen Institute; 3) Describe the validity of the curriculum for teaching speaking skills at the Islamic Pen Institute.The research method is research and development in the form of Borg and Gall. It is ten steps, but the researcher only takes the first step to the fifth. The result of the research is that: (1) Designing the curriculum for teaching speaking skills is analyzing the needs by interviewing Arabic language teachers at this institute, collecting data, i.e. collecting curriculum data from the results of the interview and a desk study, designing the production, validating the Arabic language teaching curriculum expert, correcting the first production, and group production. The result of the curriculum expert's approval is 88.46% with an excellent rating, while the confirmation from Arabic language teachers is 81% with a very good rating; (2) Specifications of the curriculum for teaching speaking skills: Objectives: Focus on speaking Arabic about activities in the institute such as when teaching or specific situations, Content: Suitable for the objectives in the form of basic topics. Some of the content is from contemporary Arabic language teaching books and some from Arabic language teachers, Method: Direct method, role-playing, presenting the story, and expressing images, Evaluation: Suitable for the material, method, and time available for evaluation; (3) Validity of production is obtained 98.3% with an excellent rating. The conclusion from this research is that the designed curriculum for teaching speaking skills is suitable for use in classroom teaching for tenth grade students at Al-Qalam Al-Islami Institute based on the result of the validity of the curriculum by Arabic language teachers.